2003
DOI: 10.1210/en.2003-0036
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing Hormone Receptor Knockout (LuRKO) Mice and Transgenic Human Chorionic Gonadotropin (hCG)-Overexpressing Mice (hCG αβ+) Have Bone Phenotypes

Abstract: Considerable attention has been paid to the role of sex steroids during periods of major skeletal turnover, but the interaction of the gonadotropic hormones, which include LH, FSH, and human chorionic gonadotropin (hCG), within bone tissue have been overlooked. The question is pertinent due to the recent detection of extragonadal expression of gonadotropin receptors. Western blotting, immunolocalization, and RT-PCR supported the presence of osteoblast LH receptors. However, osteoblast cells failed to bind [(12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 26 publications
2
31
1
Order By: Relevance
“…Taken together these data indicated that all effects found on bone density in the WT and the two genetically modified mouse models could be explained by modifications of gonadal activity. Most conspicuously, the increase in BMD seen in hCGαβ+ females was totally abolished and reversed to the same low level as in ovariectomized WT females, despite the persistent elevation of hCG in TG females (Yarram et al, 2003). It is apparent that ovarian estrogen production was the main factor determining BMD in these models.…”
Section: Bone Phenotypes Of Lurko and Hcg Tg Micementioning
confidence: 81%
See 3 more Smart Citations
“…Taken together these data indicated that all effects found on bone density in the WT and the two genetically modified mouse models could be explained by modifications of gonadal activity. Most conspicuously, the increase in BMD seen in hCGαβ+ females was totally abolished and reversed to the same low level as in ovariectomized WT females, despite the persistent elevation of hCG in TG females (Yarram et al, 2003). It is apparent that ovarian estrogen production was the main factor determining BMD in these models.…”
Section: Bone Phenotypes Of Lurko and Hcg Tg Micementioning
confidence: 81%
“…Letters ns in the hCGαβ+ ovx bar denotes that significant differences between the WT ovx and hCGαβ+ ovx groups were not found. Modified from Yarram et al (2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transgenic mice over-expressing LH but with silenced receptors did not show cognitive impairment in the Ymaze task suggesting receptor-mediated effect of LH on these behaviors (Casadesus et al, 2007). However, LH can exert some of its affects via mechanisms independent of the LH receptor and traditional downstream signaling mechanisms (West and Cook, 1992;Yarram et al, 2003). Whether or not these receptor-independent effects play a roll in this system is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%